Digital Library for Thesis According to Genisis System (Al-Mansour Journal, 2023)
Using modern technology has its impact on improving and developing the libraries and information centers. This has achieved progress in all the work of the library including the selection, preparing and recovery, a core business by the libraries of different kinds.It achieved quickness and accuracy through giving all the facilities to access information, after there were only specific points of access to reach the computerized index, which came as a result of rapid developments in modern technology, where it found with the use of computers in libraries.The Central Library of the University of Technology was able, through the completion of the requirements of computerizing index by using Winisis system, to establish the database for thesis and papers of university graduates since 1977 until 2008 and make these databases available to the users of the Central Library.The researcher used the modern system ‘Genisis’, issued by UNESCO in foreign languages, and he became able of adapting the system to work in Arabic, due to the fact that many of theses are in Arabic. He used the system through the Internet, which allows receiving data stored on the Winisis system. It supports special searching engine that is easy to use and supports research on the content of the full text using the Bauliyani logic. This is done after taking the necessary steps to build the database in the search described in detail and composing a digital library.One of the goals of modern libraries is to deliver information to the users easily and quickly to take advantage of digital libraries. It eliminates the problems they currently face when searching, the site of the University of Technology, the database that the researcher put experimentally of retrieving by the title only, where as, now it is possible to use the digital library on the site of the university by using Genisis system in searching and retrieving, and through the well-known searching engines; Google and Yahoo